A Descriptive Study On Teaching Speaking Skill Adopting Genre-Based Approach At The Second Year Of SMA N 1 Gondang Sragen In 2011/2012 Academic Year. - Armita, Iva (2012)
The current study aims at describing the teaching speaking skill adopting genre-based approach at the second year in SMA N 1 Gondang, Sragen. The objective of the research are: (1) To describe the procedure of teaching speaking skill adopting Genre-based Approach, (2) To describe the implementation of genre based approach in teaching speaking skill, (3) To identify the problems faced by the teacher in teaching speaking skill at the second year of SMA N 1 Gondang Sragen adopting Genre-based approach in 2011/2012 academic year. In this current study the writer applies at descriptive qualitative research as the type of this research.There are three methods of collecting data are observation, interview, and document. The writer did interview with the English teacher and the students of XI IPS4 class, and observed the process of speaking teaching- learning at the second year of SMA N 1 Gondang Sragen. After analyzing data, the researcher finds that (1) the procedure consists of 3 patterns. The first are BKOF, MOT, JCOT, ICOT. The second are BKOF, MOT and JCOT. The third are BOF, MOT and ICOT, (2) the implementation are are group discussion, individually task and question answer, (3) the writer also found the problems faced by the teacher, namely Physically of the Classroom Condition, Difficulties in Managing the Class, Uncompleted Facilities in the School, Lack of Student Activity, Different capability of the students, Lack of time.